ChemInform Abstract: (1, 2‐Diaminoethane‐1, 2‐diyl)bis(N‐methylpyridinium) Salts as a Prospective Platform for Designing Recyclable Prolinamide‐Based Organocatalysts. Issue 9 (February 2016) - Lisnyak, Vladislav G.; Kucherenko, Alexander S.; Valeev, Edward F.; Zlotin, Sergei G.
Abstract: A new, efficient, and recyclable organocatalyst for asymmetric cross‐aldol reactions under neat conditions in ketone—ketone, ketone—aldehyde, and aldehyde—aldehyde systems is developed.